Pre-service teachers’ inclusion of climate change education - Ronnel Joseph Tracena Competente (Institute of Advanced Engineering and Science, 2019)
Findings from the study of pre-service teachers’ (PSTs) attitudes to climate change education, knowledge of climate change and potential inclusion in their future teachings are reported in this paper. Using adopted and self-made questionnaire, a sample of 180 pre-service teachers participated in a survey study in the College of Education, University of Nueva Caceres, divided into freshmen and senior year to examine developments in their attitudes to environmental education and their knowledge of climate change. Results showed that their attitudes towards climate change education were low and their climate change science knowledge had not changed. Data on preservice teachers’ sources of information for climate change, their views on essential climate change topics for their future students and their perceptions of gaps in their own training in relation to climate change education were also examined in order to substantiate the survey data. Results show that there is a need to triangulate climate change education not only in the program outcomes but also to the student and faculty development programs. Further results are discussed in this paper.